NOVEL AVIFAUNAL INVENTORY OF GUNUNG Q, AN OVERLOOKED OUTLYING MOUNTAIN RANGE IN PAPUA, INDONESIA - Mohammad irham; Yong Chee Keita Sin; Chen Xi Sng; Johan Gustiar Imbenai; Mochtar Tanassy; Frank E. Rheindt (BRIN Publishing (Penerbit BRIN), 2025)
Papua is the second-largest island on earth and a major centre of biodiversity, but remainsunderexplored. The island’s montane fauna is particularly rich in endemic species, but most of itsexploration has historically focused on the main cordillera that stretches across the island from east towest. Exploration of a number of smaller, isolated outlying mountain ranges has recently produced asubstantial amount of new species discovery. We explored the avifauna of Gunung Q, an isolatedoutlying mountain in the province of Papua (Jayapura) rising to 1800m, with no topographicconnection to any nearby mountain range. To the best of our knowledge, Gunung Q has never previouslybeen inventoried by biologists. Our fieldwork, which encompassed exploration of the mountain only upto 1100m, produced various new regional records and suggests that Gunung Q has the potential forsubstantial undiscovered endemism at higher elevations.